Теоретично-методичні аспекти оцінки конкурентних позицій банків на фінансовому ринку - Соколова, Л. В.; Бабкін, С. В.; Попова, Т. О. (ХНУРЕ, 2015)
This scientific work is devoted to the study of the existing methods for assessing the competitive position of commercial banks in the domestic financial services market. Assessment of the competitive position of the bank as a whole is important for the development of an effective competitive strategy of the bank. To better determine the competitive position of commercial banks need to carefully and reasonably choose the most appropriate method for your situation.
Keywords: оцінка конкурентних позицій банків; банк; конкурентна позиція; фінансовий ринок